2015
DOI: 10.4049/jimmunol.1500209
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 Regulates the Differentiation and Function of Myeloid-Derived Suppressor Cells via Targeting Runx1

Abstract: Myeloid-derived suppressor cells (MDSCs) play a critical role in tumor-associated immunosuppression, thus affecting effective immunotherapies for cancers. However, the molecular mechanisms involved in regulating the differentiation and function of MDSCs remain largely unclear. In this study, we found that inhibition of microRNA (miR)-9 promoted the differentiation of MDSCs with significantly reduced immunosuppressive function whereas overexpression of miR-9 markedly enhanced the function of MDSCs. Notably, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 46 publications
5
73
0
Order By: Relevance
“…We read with interest the article by Tian et al, 1 describing the role of MicroRNA-9 (miR-9) in the regulation of myeloid-derived suppressor cell (MDSC) differentiation and function by targeting the runt-related transcription factor 1 (Runx1). This finding has revealed posttranscriptional regulation of Runx1 by miR-9.…”
Section: Microrna-9 Promotes Cell Proliferation By Regulating Runx1 Ementioning
confidence: 99%
“…We read with interest the article by Tian et al, 1 describing the role of MicroRNA-9 (miR-9) in the regulation of myeloid-derived suppressor cell (MDSC) differentiation and function by targeting the runt-related transcription factor 1 (Runx1). This finding has revealed posttranscriptional regulation of Runx1 by miR-9.…”
Section: Microrna-9 Promotes Cell Proliferation By Regulating Runx1 Ementioning
confidence: 99%
“…A microRNA microarray in Whole β-Glucan Particles (WGP)-treated MDSCs isolated from the spleen of Lewis lung carcinoma bearing mice identified 61 miRNAs that were downregulated whereas 40 miRNAs were upregulated (Tian et al, 2015). Specifically, the authors identified miR-9 as an important regulator of Runx1 (runt-related transcription factor) as a direct, bona fide target of miR-9 (verified by 3'UTR luciferase reporter assay in HEK-293T cells).…”
Section: β-Glucan Inhibits Mir-9 Expression In Mouse Macrophage Cellsmentioning
confidence: 98%
“…These data demonstrated that IL-1 and IFN-γ differentially regulate the β-glucan-induced Th responses in human DCs. Splenic MDSC from 100 ug mL −1 for 24 h; whole (Tian et al, 2015) miRNA microarray assay downregulated miRNAs tumor-bearing mice β-glucan particles from GEO accession number -focused on mmu-miR-9 S. Cerevisiae GSE67578; Identified Runx1, a CREB mRNA and protein transcription factor involved in differentiation of MDSCs, as a direct, bona fide target of miR-9. CREB, transcription factor, suppressed miR-9 transcription.…”
Section: Microarray Analysis In Human Monocyte-derived Dendritic Cellsmentioning
confidence: 99%
See 2 more Smart Citations